Optimising Healthcare Delivery: The Role of Centralised Electronic Health Records in Enhancing Patient Care and Efficienc - Kotre, Siddhi Santosh (Journal of Advanced Research in Information Technology, Systems and Management; Vol 9 No 1 (2025): Journal of Advanced Research in Information Technology, Systems and Management, 2025)
In the rapidly evolving healthcare landscape, the need for innovative solutions to enhance patient care and streamline operational efficiency has never been more critical. Centralised Electronic Health Records (EHR) have emerged as a ground- breaking tool in this transformation, revolutionising the way patient data is stored, accessed, and shared. By consolidating disparate health records into a unified, easily accessible system, EHRs eliminate the inefficiencies and risks associated with paperbased records and fragmented data. This seamless integration fosters real-time communication among healthcare providers, ensuring that patients receive timely, well-coordinated care. Furthermore, centralised EHR systems have the potential to significantly reduce administrative costs, minimise medical errors, and improve decision-making processes.